2021
DOI: 10.1093/rb/rbab018
|View full text |Cite
|
Sign up to set email alerts
|

Click chemistry-based pre-targeting cell delivery for cartilage regeneration

Abstract: A fraction of the OA patient population is affected by post-traumatic osteoarthritis (PTOA) following acute joint injuries. Stopping or reversing the progression of PTOA following joint injury could improve long-term functional outcomes, reduced disability, and medical costs. To more effectively treat articular cartilage injury, we have developed a novel cell-based therapy that involves the pre-targeting of apoptotic chondrocytes and the delivery of healthy, metabolically active chondrocytes using click chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Dual functionalization of PEG by transcyclooctene (TCO) and apoptotic binding peptide (ApoPep-1) led to the development of a crosslinker that binds to apoptotic chondrocytes of injured cartilage explant and methyltetrazine-bearing metabolically active chondrocytes through ApoPep-1 and TCO, respectively. This click chemistry-based pretargeting approach resulted in significant reduction of cartilage degeneration and increased ECM synthesis [ 72 ]. Since TCD is a developing approach for repairing cartilage defects, its integrative capacity is not well-studied yet, but is expected to be explored in early future.…”
Section: Recruiting Cells To Achieve Csimentioning
confidence: 99%
“…Dual functionalization of PEG by transcyclooctene (TCO) and apoptotic binding peptide (ApoPep-1) led to the development of a crosslinker that binds to apoptotic chondrocytes of injured cartilage explant and methyltetrazine-bearing metabolically active chondrocytes through ApoPep-1 and TCO, respectively. This click chemistry-based pretargeting approach resulted in significant reduction of cartilage degeneration and increased ECM synthesis [ 72 ]. Since TCD is a developing approach for repairing cartilage defects, its integrative capacity is not well-studied yet, but is expected to be explored in early future.…”
Section: Recruiting Cells To Achieve Csimentioning
confidence: 99%
“…e results employing autogenic cartilage implanted in a pos-traumatic osteoarthritis defect indicated favorable results in cartilage damage specifically [31]. Furthermore, more advanced methods were used to improve articular cartilage regeneration using bioactive molecules.…”
Section: Injectable-dependent Approachesmentioning
confidence: 99%
“…Microfracture ± HA ± haMPCs [55] AD-MSCs ± allogeneic cartilage from fresh cadavers [56] Intra-articular injection of autologous SVF [57] Intra-articular injections of allogeneic haMPCs [58]…”
Section: Clinical Studiesmentioning
confidence: 99%
“…For this purpose, they developed a dual-acting system that first targets apoptotic chondrocytes by a PEG polymer carrier conjugated with apoptosis-targeting peptide-1 (ApoPep-1) and trans-cyclooctene (TCO) and, second, delivers metabolically active chondrocytes. The results of the in vitro assessments and ex vivo studies using human cartilage explant PTOA models showed promising outcomes in specifically targeting and treating cartilage injury [ 56 ]. Moreover, more complex technologies were applied to optimize articular cartilage regeneration via bioactive molecules.…”
Section: Tissue Engineering Strategies For Articular Cartilage Regenerationmentioning
confidence: 99%